Predictive value of chart‐based frailty evaluation for lung transplant candidates. Issue 1 (23rd September 2021) - Gee, Serina; Lee, Yoon; Shah, Aloukika; Izadmehr, Ehsan; Belperio, John; Shino, Yusaku; Weigt, Sam; Goldwater, Deena; Schaenman, Joanna
Abstract: Frailty, defined as a state of decreased physiologic reserve, has been correlated with poorer outcomes after hospitalization or surgery. Studies in lung transplant patients have associated frailty with an increased risk of post‐transplant mortality; however, a unified approach is lacking. The identification of frail patients can help clinicians pre‐emptively target modifiable risk factors and may facilitate risk stratification. The Frailty Risk Score (FRS) is a chart review‐based approach based on eight symptoms and four laboratory biomarkers. We applied this method in a retrospective study to investigate its utility in predicting post‐transplant lung outcomes. Eighty‐four lung transplant recipients were evaluated, including 51 older (≥ 60) and 33 younger (< 60) patients. Median FRS score was 3.9, with 63 categorized as frail (75%) and 21 as non‐frail (25%), using a previously published cut‐off of ≥3 to define frailty. A high FRS was associated with readmission in the first year after transplantation and with the number of readmissions. There was also an association between FRS score and death ( p  = .047). FRS may be a viable tool in the assessment of lung transplant candidates. Frail patients may benefit from earlier referral and targeted therapy prior to transplant, as well as close post‐transplant follow‐up.